Kajian terhadap hubungan ciri-ciri inovator pengurusan dengan keinovatifan individu di Politeknik Kementerian - Roshamimi , Faisal (2011)
This study is looking for a combination of the characteristics of managerial innovator and individual innovativeness among middle managers in polytechnics, Ministry of Higher Education Malaysia (MOHE).The objective of this study was to investigate how the managerial innovator characteristics influence on individual innovativeness and what is the most important factor to be emphasized and encouraged to enhance individual innovativeness in human resource development in polytechnic. This study also suggests that the model that can be used to predict the level of individual innovativeness based on the characteristics of managerial innovator.Besides that,this study also describes the correlation between the managerial innovator characteristics that influence individual innovativeness based on the background demographic of middle managers in polytechnics MOHE.With a sample of 300 usable questionnaire,responses from the middle managers, this study answers five key questions using factor analysis, the single mean t-test, ANOVA,correlation analysis 'Pearson' and multiple regression.The study has shown that the overall level of the characteristics of managerial innovator and individual innovativeness among middle managers in the polytechnics MOHE are high. The findings from the correlation analysis 'Pearson' have proved that the attitude toward change(positive attitude towards changes)has the highest correlation followed by the morale of values(values of responsibility,sincerity/integrity),orientation toward personality changes,and finally professionalism (ethical standard and professional standard orientation) with individual innovativeness (seeking for information).From the multiple hierarchical regression analysis,the results show that age is significantly moderates the relationship between the characteristics of managerial innovator and individual innovativeness.The regression function model to be used to predict Individual Innovativeness(seeking for information) based on the characteristics of managerial innovator is; Individual Innovativeness(seeking for information) = 46.467 – 0.112(KO reference group orientation)+ 0.231(SP positive attitude towards changes)+ 0.136(SP orientation toward personality changes)+0.190 NM responsibility)-0.246(age). Qualitative data was transcribed and categorized to identify themes and patterns in which the ten respondents from the Director/Management Representative were interviewed.From the findings of qualitative data analysis,the level of innovator characteristic and individual innovativeness among middle managers at polytechnic are medium.Management support,such as motivation, creative environment, training, good communication and competition in work promotion can be a factor in maintaining and strengthening managerial innovator characteristic to enhance the innovativeness of middle managers in polytechnics.Government support,opportunity and the policy,good economic environment and competition with other educational institutions can be push factors to boost the innovativeness of middle managers.